Synergistic surfactant-assisted [EMIM]OAc pretreatment of lignocellulosic waste for enhanced cellulose accessibility to cellulase. (15th June 2017) - Goshadrou, Amir; Lefsrud, Mark
Graphical abstract: Highlights: Beech wood waste was pretreated using [EMIM]OAc with/without surfactant assistance. Pretreated materials were thoroughly characterized by semi-quantitative techniques. Enhanced cellulose accessibility to enzyme had the most impact on hydrolysis yield. Enzymatic hydrolysis of the wood was improved by ∼21% upon surfactant assistance. Ethanol yield from the wood was improved by ∼13% upon surfactant assistance. Abstract: The present study investigated for the first time the efficacy of surfactant-assisted ionic liquid 1-ethyl-3-methylimidazolium acetate ([EMIM]OAc) pretreatment of beech wood waste for enhanced ethanol production. The ionic liquid (IL) pretreatment included wood dissolution at 120 °C and 5% solid loading for 3 h followed by regeneration using water as an anti-solvent. The substrate was initially presoaked in different concentrations of surfactant solution (2%, 4%, 6% w/w) prior to IL pretreatment. Tween 20, Tween 80 and polyethylene glycol 4000 (PEG) surfactants were tested and the results revealed major improvements in the yield of enzymatic hydrolysis. More than 91% enzymatic digestibility was achieved for the PEG (2%)-assisted IL-pretreated wood, while yields from untreated and IL-pretreated wood were only 6.0% and 75.2%, respectively. A maximum ethanol yield of 82.1% was obtained. Comprehensive characterization of the pretreated materials using semi-quantitative methods indicated that synergistic surfactant-assisted [EMIM]OAc pretreatment significantly increased cellulose accessibility to cellulase and decreased the hemicellulose and lignin contents.